Penerapan Data Mining Untuk Menentukan Penerima Jaminan Kesehatan Daerah (Jamkesda) Dengan Metode Decision Tree (C4.5) - Ismasari Nawangsih; Fazri Setyawan (Jurnal SIGMA, 2019)
The Regional Health Insurance (JAMKESDA) effort is a public health maintenance whose financing is managed in an integrated manner. In addition, the Regional Health Insurance (JAMKESDA) is a guarantee program for payment of health service costs provided by the Regional Government. The method applied in determining the Regional Health Insurance recipient (JAMKESDA) is a decision tree method and using the C.45 Decission tree algorithm is a decision tree classification method that is mostly used because it has a major disability that can produce decision pchons that are easy to implement, have a high degree of accuracy acceptable, efficient in handling discrete and numeric type attributes. The results of this study indicate that the application of the decision tree method with the C4.5 algorithm makes selection faster, more precise and accurate in selecting prospective regional health insurance (JAMKESDA). Keywords : Jamkesda, data mining, decision tree, c4.5